Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1111/j.1751-0813.1998.tb10128.x
|View full text |Cite
|
Sign up to set email alerts
|

Snake bites recorded by veterinary practices in Australia

Abstract: ObjectiveTo determine the extent of the snake bite problem in domestic animals, its regional significance and the effects of antivenom treatment. DesignA questionnaire was designed seeking information on the number and type of domestic animals referred, whether treated or untreated, type of snakes and management of the bite.Procedure The survey form was sent to 10% of veterinary surgeons, selected at random throughout Australia. ResultsThe response of 106 veterinary surgeons revealed that snake bite in domesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
58
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 6 publications
(9 reference statements)
2
58
0
2
Order By: Relevance
“…The use of any other modality for diagnosis was inconsistent and few clinics reported regular use of SVDKs, consistent with previous studies in domestic species 14 and humans. 34 The current study attributes poor use of venom detection kits predominantly to expense, supporting a previous hypothesis made by Mirtschin et al 13 Excess time needed to run venom detection tests and perceived lack of accuracy were also noted as strong deterrents by veterinarians in New South Wales.…”
Section: Treatmentsupporting
confidence: 74%
See 3 more Smart Citations
“…The use of any other modality for diagnosis was inconsistent and few clinics reported regular use of SVDKs, consistent with previous studies in domestic species 14 and humans. 34 The current study attributes poor use of venom detection kits predominantly to expense, supporting a previous hypothesis made by Mirtschin et al 13 Excess time needed to run venom detection tests and perceived lack of accuracy were also noted as strong deterrents by veterinarians in New South Wales.…”
Section: Treatmentsupporting
confidence: 74%
“…6,14,27 Within this study, RBBS, combined with Brown snakes, are the most geographically (indicated by the number of clinics encountering these species) and clinically (indicated by the percentage of envenomations attributed to these species) common species implicated in snake envenomations within New South Wales. Brown snakes have previously been reported as a common source of envenomation in New South Wales for domestic species and humans, 13,14,28 but RBBS have only been discussed as rare sources of envenomation and have even been considered a species that does not pose a medical threat to domestic animals. 6 The current study reveals that the envenomation syndrome reportedly produced by the RBBS species occurs as commonly as any other reported snake envenomation syndrome in dogs within New South Wales.…”
Section: Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Although snakes are the most common cause of such human fatalities (White, 2000), the number of deaths has been declining annually in recent decades (Currie, 2004;Mirtschin, Masci, Paton & Kuchel, 1998;Sutherland & Leonard, 1995). Arthropod bites (e.g., spiders, ants, centipedes), although medically significant, seldom result in death.…”
Section: Dangers Of Outdoor Recreationmentioning
confidence: 99%